Incidence and risk factors for recurrent IgA nephropathy after kidney transplantation: A multicenter cohort study from Denmark - Mette Thrane Øhrstrøm; Michael Dyrehauge Schultz; Claus Bistrup; Henrik Birn (PLoS ONE, 2026)
Background Recurrent immunoglobulin A nephropathy after kidney transplantation remains a major clinical challenge, but risk factors are not fully defined. This study aimed to evaluate the incidence of biopsy-proven recurrent IgAN and identify risk factors for recurrence in a contemporary Scandinavian cohort. Methods We conducted a multicenter cohort study including adult patients with biopsy-proven immunoglobulin A nephropathy who received a first kidney-only transplantation between 1990 and 2020 across two Danish transplantation centers. Recurrence incidence and associations with clinical and donor-related characteristics were assessed during follow-up. Results A total of 118 recipients were followed for a median of 5.5 years. Biopsy-confirmed recurrence occurred in 14% of patients, corresponding to a cumulative incidence of 16% at 10 years post-transplantation. Younger age at immunoglobulin A nephropathy diagnosis, faster progression to kidney failure, and receipt of a kidney from a living or genetically related donor were independently associated with an increased risk of recurrence. Maintenance post-transplant steroid use was not associated with recurrence. Recurrent immunoglobulin A nephropathy was associated with an increased risk of graft failure compared with non-recurrent disease (unadjusted HR 3.8; adjusted HR 6.7). Conclusions Recurrence of IgAN after kidney transplantation remains a clinically significant challenge, associated with younger age, rapid progression to KF, and transplantation from living or genetically related donors. Maintenance post-transplant steroid use was not associated with recurrence risk in this cohort. Larger and more diverse cohorts are warranted to clarify donor-related risk, strengthen the evidence on immunosuppressive protocols and guide strategies to improve graft outcomes.